2004
DOI: 10.1534/genetics.104.026997
|View full text |Cite
|
Sign up to set email alerts
|

The Inheritance and Evolution of Leaf Pigmentation and Pubescence in Teosinte

Abstract: To investigate the genetic mechanisms that underlie morphological evolution in natural populations, we employed QTL mapping to dissect the inheritance of leaf sheath characters that distinguish Chalco from Balsas teosinte. Abundant macrohairs (trichomes) and intense anthocyanin accumulation are found in Chalco teosinte sheaths whereas Balsas teosinte leaf sheaths are green and glabrous. These character states may represent adaptations to the cooler highland (Chalco) vs. warmer middle-elevation (Balsas) climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
82
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 45 publications
17
82
0
Order By: Relevance
“…Consistent with previous work suggesting adaptive introgression from teosinte, the Mesoamerican highland population shares a larger proportion of SNPs identified as adaptive in teosinte . We also see more F ST outliers in Mesoamerica in regions introgressed from teosinte and that overlap with QTL for differences between parviglumis and mexicana (Lauter et al 2004;Hufford et al 2013). Finally, although our SNP data are enriched in low-copy genic regions, our results are consistent with both genome-wide association studies in maize (Wallace et al 2014) and local adaptation in teosinte in finding an excess of putatively adaptive SNPs in intergenic regions of the genome.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Consistent with previous work suggesting adaptive introgression from teosinte, the Mesoamerican highland population shares a larger proportion of SNPs identified as adaptive in teosinte . We also see more F ST outliers in Mesoamerica in regions introgressed from teosinte and that overlap with QTL for differences between parviglumis and mexicana (Lauter et al 2004;Hufford et al 2013). Finally, although our SNP data are enriched in low-copy genic regions, our results are consistent with both genome-wide association studies in maize (Wallace et al 2014) and local adaptation in teosinte in finding an excess of putatively adaptive SNPs in intergenic regions of the genome.…”
Section: Discussionsupporting
confidence: 85%
“…The modeling highlights that our outlier approach may not detect traits undergoing convergent evolution if the genetic architecture of the trait is such that mutation at a large number of nucleotides would have equivalent effects on fitness (i.e., adaptive traits have a large mutational target). While QTL analysis suggests that some of the traits suggested to be adaptive in highland conditions may be determined by only a few loci (Lauter et al 2004), others such as flowering time (Buckler et al 2009) are likely to be the result of a large number of loci, each with small and perhaps similar effects on phenotype. Future quantitative genetic analysis of highland traits using genome-wide association methods may prove useful in searching for the signal of selection on such highly quantitative traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Satish et al [94] identified eight QTLs (quantitative trait loci) for trichome density using sorghum, two of which were specific for upper leaf surface, the remaining six specific to the lower leaf surface. Four QTL were identified in maize for trichome density by Lauter et al [98], several of which were syntenic to those determined in sorghum. By breeding for increased trichome densities and beneficial morphology, improved resistance to insect herbivory, specific per host-herbivore relationship can be achieved.…”
Section: Energy and Pesticidesmentioning
confidence: 99%
“…Mexicana also has red, hairy leaf sheaths in contrast to the green and glabrous leaf sheaths of parviglumis [1], traits thought to be important for adaptation to the cool temperatures of the Mexican highlands [5]. Differentiation at the morphological level is accompanied by genetic divergence [3], [4].…”
Section: Introductionmentioning
confidence: 99%